The Use Of Response Surface Methodology (RSM) To Optimize The Twist Drill Geometry In Single Shot Drilling Of Stacked Alumina-Carbon Composite Layer - Mohd Adnan, Muhammad Aimi (Universiti Sains Malaysia, 2018)
Stacked up drilling is being practiced widely in the aerospace industry, but the compatibility of the drill to compensate the widely differing properties of composite and metal is still a major challenge to the industry. In this study, the effect of the twist drill geometry and drilling parameters are being investigated based on the generation of thrust force signature during drilling of CFRP/Al. The study was aimed to establish the optimum values of those testing parameters through the use of statistical method of response surface methodology (RSM) by central composite design (CCD) is used to select twenty runs of experiment to evaluate the significance of tool geometry on thrust force during the drilling operation. The CCD is a very effective design for use a second-order response surface model. Based on ANOVA, it is found that the maximum thrust force and surface roughness is the most influencing factor of optimum value for tested parameters for Aluminum and CFRP. Through the analysis of thrust force and surface roughness, it is concluded that the optimum tool parameters selection includes primary clearance of 6°, point angle of 130°, and chisel edge angle of 45°. The parameters for speed and feed rate are fixed at 2600 rpm speed and 130 mm / min feed rate.